2019
DOI: 10.1007/s13524-019-00798-y
|View full text |Cite
|
Sign up to set email alerts
|

When and Where Birth Spacing Matters for Child Survival: An International Comparison Using the DHS

Abstract: A large body of research has found an association between short birth intervals and the risk of infant mortality in developing countries, but recent work on other perinatal outcomes from highly developed countries has called these claims into question, arguing that previous studies have failed to adequately control for unobserved heterogeneity. Our study addresses this issue by estimating within-family models on a sample of 4.5 million births from 77 countries at various levels of development. We show that aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 47 publications
4
71
1
Order By: Relevance
“…Although several studies have found that the very shortest intervals, 0-5 months, increase the risk of preterm birth, Shachar et al (2016) and Class et al (2017) also found that IPIs of less than 18 months increased the risk of preterm birth, though not the risk of LBW or SGA. Research on infant mortality in less developed contexts using sibling comparison models has found that short birth intervals matter at lower levels of development but that the negative effects are substantially weaker at higher levels of development (Molitoris 2017;Molitoris et al 2019).…”
Section: Previous Empirical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have found that the very shortest intervals, 0-5 months, increase the risk of preterm birth, Shachar et al (2016) and Class et al (2017) also found that IPIs of less than 18 months increased the risk of preterm birth, though not the risk of LBW or SGA. Research on infant mortality in less developed contexts using sibling comparison models has found that short birth intervals matter at lower levels of development but that the negative effects are substantially weaker at higher levels of development (Molitoris 2017;Molitoris et al 2019).…”
Section: Previous Empirical Researchmentioning
confidence: 99%
“…As a result, it is important to adjust for all factors that are shared among siblings in the sibling group, in order to try to isolate the effects of birth intervals net of confounding factors. As already discussed, when this approach is applied, the long-standing conclusions regarding the negative effects of short and long birth intervals are no longer so clear (Ball et al 2014;Shachar et al 2016; Barclay andKolk 2017, 2018;Class et al 2017;Hanley et al 2017;Koullali et al 2017;Molitoris et al 2019).…”
Section: Potential Mechanisms Linking Interval Length To Poor Outcomesmentioning
confidence: 99%
“…5 There is little research on modifying interpregnancy inter vals; possible strategies to change such intervals could include educational programmes, cash transfer programmes, and contraception provision programmes, which have been shown to reduce pregnancy rates in LMICs. 6,7 Several studies have examined the association between interpregnancy interval and subsequent adverse perinatal and maternal outcomes, such as small-for-gestationalage birth, 8 preterm birth, 9 low birthweight, 10 child mortality, 11,12 maternal death, 13 and, to a lesser extent, stillbirth. 14 Although many of these studies have found strong associations between short interpregnancy intervals and adverse birth outcomes, there is ongoing debate regarding whether or not the relationship is causal.…”
Section: Introductionmentioning
confidence: 99%
“…In the foreign sources on the aspects of demographical questions of the birth and death rate there are also publications on the researches of scientists, based on the national peculiarities of the family institute and the role of the government regulator in this process in different time periods of analytical researches [2,3], which makes this topic actual in the global aspect.…”
Section: A Results Of Theoretical Researchesmentioning
confidence: 99%